The Impact of Digitalization on the Human Development Index in ASEAN - Ahmad Mahfudj; Siti Aisyah (Universitas KH. Abdul Chalim Mojokerto, 2025)
Digital transformation has driven economic modernization, requiring improvements in human well-being while ensuring energy consumption aligns with the Sustainable Development Goals. This study investigates the impact of digitalization, education, per capita income, renewable energy consumption, and economic growth on the Human Development Index (HDI) in seven ASEAN countries Indonesia, Malaysia, Singapore, Thailand, Cambodia, the Philippines, and Laos during 2015–2022, using panel data analysis and a fixed effects model. Data were obtained from the World Bank and the United Nations Development Programme. The findings reveal that individual internet usage, education expenditure, and economic growth significantly enhance HDI, highlighting the role of digital connectivity in improving quality of life. However, the study is subject to certain limitations, including the relatively short time frame, potential data availability issues, and the assumption of homogeneity across countries within the fixed effects model. Acknowledging these constraints is essential for contextualizing the findings and guiding future research toward more comprehensive, long-term, and heterogeneous analyses.